Saberes, fazeres e sabores: o amanhecer da feira livre Bragantina - ROSARIO, Samuel Antonio Silva do (Universidade Federal do Pará, 2020)
This video presents the dawn in the free trade fair of Bragantina, showing the diversities of knowledge, crafts and flavors that are in this environment, one day of the month of March 2017, from the logic of the fair. In the video, several spaces of the fair are used, in the municipality of Bragança / Pará, among them, flour and its derivatives, fish and shellfish, fruit and vegetables, handicrafts and medicinal products from forests and rivers. In capturing the images, a Nikon Coolpix P520 camera was used.